Comparison of quadrate and transect survey methods to evaluate pastoral value (PV) in SE Sardinian rangelands - Vacca G.; Camarda I.; Brundu G.; Sanna F.; Caredda S.; Re G.A. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Pastoral resources are considered economically less profitable and less valuable from the environmental point of view, when compared to forest resources. This underestimation is in contradiction with the new important services that are attributed to grazing resources. Natural or semi-natural rangelands, in addition to providing forage resources, similarly to forest resources, represent fundamental ecosystems for the maintenance of biodiversity. The present study reports a comparison of three survey methodologies used to determine the pastoral value of grassland plant communities, as well as their species composition and biodiversity value. The research aimed also to remark the importance of integrating different methodological approaches to provide effective tools for a sustainable management of grassland. Surveys to evaluate the plant communities were based on Daget-Poissonet (transect), Braun-Blanquet methodology (quadrate) and Argenti et al. (transect). According to our results there were significant differences between the three methods, with diverse accuracies in terms of the total number of recorded species and pastoral values.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)